Sudden Death Post Covid-19 Infection - Ramlachan, Nicole; Muhammad, Mujahidah (European Journal of Applied Sciences, 2023)
The SARS-CoV-2 virus-caused COVID-19 pandemic has had a substantial impact on world health, with respiratory symptoms receiving the most attention. Emerging research, however, reveals a possible relationship between COVID-19 and sudden cardiac death (SCD). The purpose of the present study is to investigate the link between sudden death and COVID-19 infection, highlighting the various mechanisms and risk factors involved. Understanding this relationship is critical for identifying high-risk individuals and implementing appropriate preventive and treatment solutions. The COVID-19 pandemic has created significant obstacles to global healthcare systems. While COVID-19 primarily affects the respiratory system, it has become clear that the virus can also harm other organs, including the cardiovascular system. Sudden cardiac death, a serious and often fatal occurrence, has been documented in certain COVID-19 patients during the acute phase or during recovery. There have been reports and research indicating a possible link between long COVID and heart difficulties. Long COVID refers to the ongoing symptoms and consequences that some people have after healing from COVID-19’s acute phase. While COVID-19 was initially studied for its respiratory effects, it has since been discovered that the virus can damage various organ systems, including the cardiovascular system. It is important to emphasize that the precise processes causing these cardiac problems in long COVID are unclear. Direct viral harm to the heart, immune-mediated inflammation, and irregular blood coagulation are additional possibilities. More research is being conducted to better understand COVID-19’s long-term impact on the cardiovascular system.